Supply chain for sustainable renewable energy from biomass. Issue 4 (22nd August 2019) - Ji, Jirasak; Nananukul, Narameth
A sustainable-energy policy requires the development of economical and sustainable renewable energy systems. This research focuses on the feasibility of developing a sustainable resource supply chain plan, by using available biomass as a resource for producing electricity in the Loei province, Thailand. A mathematical model has been proposed to determine suitable locations for the biomass power plants, the optimal biomass production, and supplier allocation that result in the lowest operating cost to meet the electricity demand. The availability of different types of biomass, different modes of transportation, and electricity consumption in the Loei province is used to develop the optimisation model. An extended model is also proposed to deal with the perishability of biomass. The proposed models can be used and applied by decision makers to perform different types of analysis in order to assist decision making on the location of biomass plants as well as in the distribution plan.